De l’eau mise en bouteille. Chapitre 1 - Gay Hawkins; Emily Potter; Kane Race (Revue d'anthropologie des connaissances)
Plastic Water documents the emergence and immense expansion of water packaged in plastic bottles. It focuses on plastic bottles as open-ended, unfinished objects that are always embedded in local situations and practices. It addresses the role of material objects in the construction of water markets relying on fieldwork in three big Asian cities and unpacks the specific properties of plastic bottles. It accounts for the success of plastic bottles in reconfiguring the daily practices of drinking; the streamlining of international beverage markets; and the development of political campaigns contesting bottled water and the never-ending accumulation of plastic waste it generates.Céline Granjou provides here a translation of the introduction and first chapter of the book, while Baptiste Monsaigeon is the author of the in-depth review of the book published in the same issue of the Revue d’anthropologie des connaissances. This fantastic book is located at the crossroads of the sociology of material objects and sociology of markets; it is a wonderfully clear and bright introduction to the role of material objects and industrial technologies in constituting socio-economic groups and practices, as well as forms of political contestation. It also unpacks the body of knowledge from sport science and hydration research, which has largely contributed to the success of plastic water across the world.